The hippocampus and inferential reasoning: building memories to navigate future decisions - Zeithamova, Dagmar; Schlichting, Margaret L.; Preston, Alison R. (Frontiers in Human Neuroscience, 2012)
A critical aspect of inferential reasoning is the ability to form a relationship between items or events that were not experienced together. This review will consider different perspectives on the role of the hippocampus in successful inferential reasoning. Traditional research on inferential reasoning has focused on retrieval-based processes that mediate performance. To make inferences about indirect relationships between discrete events, elements of individual memories must be individually retrieved and recombined. Specialized encoding mechanisms are needed to enable this flexible retrieval. The hippocampus has been shown to discretely code events in such a way that event elements are individually accessible from memory. For this reason, recent research has also focused on hippocampal encoding processes that support inferential reasoning, including an integrative mechanism that combines information across multiple experiences. By recalling past events during the encoding of new experiences, connections can be created between newly formed and existing memories. Such derived memories extend beyond direct experience to anticipate future judgments about the relationship between items and events. Successful inference, according to this view, would result from the expression of relational knowledge acquired through hippocampally-mediated integrative encoding. We discuss this latter perspective in the context of emerging evidence linking the hippocampus to the formation of schemas as well as prospective theories of hippocampal function that suggest memories are actively constructed to anticipate future decisions and actions.